Structural Controls on Shallow Cenozoic Fluid Flow in the Otago Schist, New Zealand. (25th August 2020) - Holbek, Simon C.; Frank, Madison; Scott, James M.; Smith, Steven A. F.; le Roux, Petrus J.; Waight, Tod E.; Van Hale, Robert; Reid, Malcolm R.; Stirling, Claudine H.
Abstract : The Otago Schist in the South Island of New Zealand represents an exhumed Mesozoic accretionary prism. Two coastal areas (Akatore Creek and Bruce Rocks) south of Dunedin preserve structural and geochemical evidence for the development of postmetamorphic hydrothermal systems that involved widespread fluid-rock reaction at shallow crustal depths. The Jurassic to Triassic pumpellyite-actinolite (Akatore Creek) to upper greenschist facies (Bruce Rocks) metamorphic fabrics were crosscut by sets of regionally extensive Cretaceous exhumation joints. Many of the joints were subsequently reactivated to form networks of small-displacement (<metres) strike-slip faults containing cemented fault breccias and veins composed of hydrothermal calcite, siderite, and ankerite. Paleostress analysis performed on infrequent fault slickenlines indicates an overall strike-slip paleostress regime and a paleo-σ 1 orientation (azimuth 094°) similar to the contemporary σ 1 orientation in Otago and Canterbury (azimuth c. 110°-120°). High δ 18 O values in vein calcite (δ 18 O VPDB = 21 to 28‰), together with the predominance of Type I calcite twins, suggest that vein formation occurred at low temperatures (<200°C) in the shallow crust and was associated with strongly channelized fluid flow along the joint and fault networks. Mass-balance calculations performed on samples from carbonate alteration zones show that significant mobilisation of elements occurred during fluid flow and fluid-rock reaction. Whole-rock and in situ carbonate 87 Sr/ 86 Sr data indicate varying degrees of interaction between the hydrothermal fluids and the host rock schists. Fluids were likely derived from the breakdown of metamorphic Ca-rich mineral phases with low 87 Rb in the host schists (e.g., epidote or calcite), as well as more radiogenic components such as mica. Overall, the field and geochemical data suggest that shallow fluid flow in the field areas was channelized along foliation surfaces, exhumation joints, and networks of brittle faults, and that these structures controlled the distribution of fluid-rock reactions and hydrothermal veins. The brittle fault networks and associated hydrothermal systems are interpreted to have formed after the onset of Early Miocene compression in the South Island and may represent the manifestation of fracturing and fluid flow associated with reverse reactivation of regional-scale faults such as the nearby Akatore Fault.